Gates of Heaven - Morris, Errol (United States, 1978)
"Gates of Heaven" is the story of two California pet cemeteries transformed into an eccentric portrait of the American dream. Errol Morris began this, his first non-fiction feature, in 1978 after reading a headline in the San Francisco Chronicle: "450 Dead Pets To Go To Napa." "Gates of Heaven" follows the stories behind two pet cemeteries -- one that fails (set up by innocent Floyd McClure at the intersection of two superhighways) and the Harbert family, who apply the latest marketing concepts to the pet cemetery profession.